Even "unconscious thought" is influenced by attentional mechanisms. Issue 1 (24th January 2014) - Srinivasan, Narayanan; Mukherjee, Sumitava
Abstract In this commentary, we focus on the role of attentional mechanisms in unconscious thought. We argue that even distracted or unconscious thought is capacity limited and differences in scope of attention influence processing during unconscious thought. Attention also would influence processes at different stages in the proposed lens model. We conclude that there is a clear need to understand the role of attention to better understand conscious or unconscious thought.